Performance scores and standings during the 43rd Artistic Gymnastics World Championships, 2011 - Massidda, M.; Calò, C. M. (Journal of Sports Sciences, 2012)
Scores in artistic gymnastics are subject to changes in the rules that occur each Olympic cycle as outlined in the Code of Points, because rules influence the composition of routines and therefore performance. The aim of this study was to identify the most important routine apparatus for success in a World competition. The data were the official results for the 478 gymnasts (262 men, 216 women) who competed in the 43rd Artistic Gymnastic World Championships in 2011 in Tokyo, Japan. The factors least influenced by the technical standard of competitors were performance scores on uneven bars and balance beam for women, and those on pommel horse for men. For uneven bars, balance beam, and pommel horse, scores were consistently good predictors of final standing. Our results suggest that high scores on these apparatus have a greater influence on overall performance than scores on the other apparatus, regardless of the competitors' standard.